The Impact of Using Duolingo Print-Out Materials on English Student Vocabulary - Ilhamullah, M.; Zuhra, Cut Mulia (English LAnguage Study and TEaching, 2024)
One of the most important components in learning English is vocabulary. Many previous studies show that students experience various problems or difficulties in learning English vocabulary because the teacher's teaching techniques are less interesting and make students bored. In this case, interesting teaching techniques are needed so that students do not get bored with teaching materials. Applications and games, for example, can be applied either online or offline to make the lesson interesting. This study aims to test whether the use of Duolingo printed materials for Grade I students at SMP IT Mahyal Ulum Al-Aziziyah can improve the student's English vocabulary. The research conducted in these two classes applies true experimental design types of pretest and posttest control group design. There were four encounters in the study including pretest and posttest. The sample of this study consisted of 54 students, which was evenly distributed in each of the classes. The instruments used to collect data were pretest and posttest. The test results were analyzed using the formula proposed by Sudjana (2006). It was found that the pretest average in the experimental class was 73 and the posttest average was 92. The pretest average in the control class was 46.3 and the posttest average was 5.3. Therefore, the increase from pretest to posttest in the experimental class was 19 points. The results of this study revealed that the use of Duolingo printed materials increased students' English vocabulary effectively and helped them remember new words.